Systemic Inflammatory Response Syndrome in Patients Hospitalized for Acute Decompensation of Cirrhosis - Ariane Borgonovo; Caroline Baldin; Dariana C. Maggi; Livia Victor; Emilia T. O. Bansho; Juliana Piedade; Letícia M. Wildner; Lívia Guimarães; Maria L. Bazzo; Tamires Rocha; Esther B. Dantas-Corrêa; Camila Alcântara; et al. (Canadian Journal of Gastroenterology and Hepatology)
Background. Although recently challenged, systemic inflammatory response syndrome (SIRS) criteria are still commonly used in daily practice to define sepsis. However, several factors in liver cirrhosis may negatively impact its prognostic ability. Goals. To investigate the factors associated with the presence of SIRS, the characteristics of SIRS related to infection, and its prognostic value among patients hospitalized for acute decompensation of cirrhosis. Study. In this cohort study from two tertiary hospitals, 543 patients were followed up, up to 90 days. Data collection, including the prognostic models, was within 48 hours of admission. Results. SIRS was present in 42.7% of the sample and was independently associated with upper gastrointestinal bleeding (UGB), ACLF, infection, and negatively related to beta-blockers. SIRS was associated with mortality in univariate analysis, but not in multiple Cox regression analysis. The Kaplan–Meier survival probability of patients without SIRS was 73.0% and for those with SIRS was 64.7%. The presence of SIRS was not significantly associated with mortality when considering patients with or without infection, separately. Infection in SIRS patients was independently associated with Child-Pugh C and inversely related to UGB. Among subjects with SIRS, mortality was independently related to the presence of infection, ACLF, and Child-Pugh C. Conclusions. SIRS was common in hospitalized patients with cirrhosis and was of no prognostic value, even in the presence of infection.